2015
DOI: 10.1016/j.schres.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparing time use in individuals at different stages of psychosis and a non-clinical comparison group

Abstract: Social functioning difficulties are a common and disabling feature of psychosis and have also been identified in the prodromal phase. However, debate exists about how such difficulties should be defined and measured. Time spent in structured activity has previously been linked to increased psychological wellbeing in non-clinical samples and may provide a useful way of assessing social functioning in clinical settings. All three clinical groups spent significantly fewer hours per week in structured activity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 25 publications
1
85
1
Order By: Relevance
“…The TUS is a semi‐structured interview assessing hours per week spent in a range of structured activities (work, education, voluntary work, childcare, housework, leisure, and sports) over the past month. On average, a non‐clinical group aged between 16 and 36 years engage in 63.49 hr of structured activity per week, and activity levels below 30 hr are indicative of poor social functioning (Hodgekins et al ., ). The TUS is suitable for use with both children and adults.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The TUS is a semi‐structured interview assessing hours per week spent in a range of structured activities (work, education, voluntary work, childcare, housework, leisure, and sports) over the past month. On average, a non‐clinical group aged between 16 and 36 years engage in 63.49 hr of structured activity per week, and activity levels below 30 hr are indicative of poor social functioning (Hodgekins et al ., ). The TUS is suitable for use with both children and adults.…”
Section: Methodsmentioning
confidence: 97%
“…Scores below 50 are indicative of poor functioning. Clinicians also completed the Time Use Survey (TUS; Hodgekins et al ., ) in relation to their clients. The TUS is a semi‐structured interview assessing hours per week spent in a range of structured activities (work, education, voluntary work, childcare, housework, leisure, and sports) over the past month.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, UHR individuals may also perceive less benefits or more barriers to getting exercise, and may not engage in exercise that requires social interaction compared to healthy individuals [100]. Another cross sectional study found that UHR and first episode schizophrenia patients spend less time in structured physical activities, and that this is related to greater social withdrawal [101]. A large review and meta-analysis suggests that adolescents at risk for psychosis are less physically active and often engage in poor health behaviors compared to typically developing adolescents, including an increased rate of tobacco and alcohol use [14].…”
Section: Exercise In Risk Populationsmentioning
confidence: 99%
“…14,15,16 In addition, UHR individuals report less motivation for getting exercise, and engage in exercise that requires little social interaction compared to healthy individuals. 17,18 Adolescents at risk for psychosis are less physically active and often engage in poor health behaviors compared to typically developing adolescents, including an increased rate of tobacco and alcohol use. 19 Taken together, individuals at risk for psychosis appear to be less physically active than typically developing young adults and this may have an impact on other markers of health and functioning.…”
Section: Introductionmentioning
confidence: 99%